2017
DOI: 10.1007/s12104-017-9728-9
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C, 15N backbone assignment of the human heat-labile enterotoxin B-pentamer and chemical shift mapping of neolactotetraose binding

Abstract: The major virulence factor of enterotoxigenic Escherichia coli (ETEC) is the heat-labile enterotoxin (LT), an AB5 toxin closely related to the cholera toxin. LT consists of six subunits, the catalytically active A-subunit and five B-subunits arranged as a pentameric ring (LTB), which enable the toxin to bind to the epithelial cells in the intestinal lumen. LTB has two recognized binding sites; the primary binding site is responsible for anchoring the toxin to its main receptor, the GM1-ganglioside, while the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The partial competition of GM1 and Le x observed by Cervin et al . 30 is most likely due to allosteric cross-talk, in line with results from a recent NMR study of the homologous LTB 46 . Similarly, we found that the CT secondary binding site variant H18A exhibits increased GM1os binding.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The partial competition of GM1 and Le x observed by Cervin et al . 30 is most likely due to allosteric cross-talk, in line with results from a recent NMR study of the homologous LTB 46 . Similarly, we found that the CT secondary binding site variant H18A exhibits increased GM1os binding.…”
Section: Discussionsupporting
confidence: 84%
“…GM1 binding to CTB is known to be positively cooperative 5658 , and the small structural changes associated with cooperative binding to the primary site could easily be transmitted to the secondary binding site, for example via the helix connecting the two sites or by stabilization of the loop region comprising residues 55–60 59 . Recent NMR data for the homologous LTB from E. coli (ETEC) are consistent with such a cross-talk between binding sites 46 . Likewise, CT variant H18A shows increased GM1os affinity compared to wild-type CT, even though the mutation is in the secondary binding site.…”
Section: Discussionmentioning
confidence: 82%
“…The very same residues are present in a CT-like toxin from C. freundii, which exhibits the strongest multivalent binding to N-acetyllactosamine-terminated receptors known to date [15]. Intriguingly, these residues lie on two paths connecting the primary and secondary toxin binding sites, which have previously been implicated in allosteric cross-talk [10,26,27]. This cross-talk may not only be important for the communication between the sites, but also directly affect binding affinity and specificity, hence being at the core of the biological mechanism of the toxins.…”
Section: Discussionmentioning
confidence: 88%
“…Intriguingly, binding to N-acetyllactosamine-terminated structures was found to be synergistically enhanced when LTB-specific residues Asn94 and Ser95 were introduced together with hLTB residues 1-25 in an LTB/CTB chimera called LCTBH [14,17]. This sequence contains important determinants of the secondary toxin binding site, which have already been in the focus of previous studies [10,17,18,20,27]. In particular, residue 4 was attributed major significance since back-substitution of LTB-specific Ser4 to CTB-specific Asn4 resulted in a complete loss of the chimera's favourable binding properties [17].…”
Section: Secondary Binding Site Residues 4 7 and 18mentioning
confidence: 85%
“…Intriguingly, binding to N-acetyllactosamine-terminated structures was found to be synergistically enhanced when LTB-specific residues Asn94 and Ser95 were introduced together with hLTB residues 1-25 in an LTB/CTB chimera called LCTBH [14,17]. This sequence contains important determinants of the secondary toxin binding site, which have already been in the focus of previous studies [10,17,18,20,27]. In particular, residue 4 was attributed major significance since back-substitution of LTB-specific Ser4 to CTB-specific Asn4 (creating toxin variant LCTBK) resulted in a complete loss of the chimera's favourable binding properties [17].…”
Section: Secondary Binding Site Residues 4 7 and 18mentioning
confidence: 85%